ASAS GRADUALITAS HUKUM ISLAM DAN APLIKASINYA DALAM LEGISLASI HUKUM ISLAM DI INDONESIA (1974-2011) - Jeje Jaenudin (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
From 1974 until 2011, as many as 14 legislations covering 8 areas of the Islamic law has been enacted in Indonesia. The establishment of Islamic law taken based on the foundation and basic principles as when it is prescribed Allah to His Messenger. Such principles “ ’Adam al Haraj” , “Taqlîl al Takâlif ”, “Musâyarat bi al Maslahat” , and